Staff Development for Networked Distance Education - Tickner, Sue (Proceedings of the International Conference on Networked Learning, 2000)
Glasgow University Initiative in Distance Education (GUIDE) was established three years ago, when there were very few distance courses at the University of Glasgow. Of those, all but one were print-based. At the time of writing there are 8 distance courses or programmes running and a further 23 in various stages of planning and development. Most of the latter make use of networked learning. The teaching staff, development team, support staff and/or administrators of these programmes need new sets of skills and knowledge. As an institution-wide service set up to support distance education and promote its development, a core part of GUIDE's work is in assisting staff who are new to the concepts, processes and methods involved in setting up and running their distance education programmes. We consequently strive to identify the specific knowledge and skills these staff will need when they embark on the design and development of such a course for the first time. This includes the skills required for networked learning. This information then directs our staff development programmes. This paper sets out some of the strategies we have applied to staff development for networked distance education. It describes the success and limitations of each approach, examines some possible reasons, and grounds this in the wider context of our philosophy and practice and our understanding of the terms 'networked' and 'networked distance education'. Particular training needs which emerge from our work suggest five broad categories are most commonly needed; these will be examined with examples from our work.